Accountability and Transparency of Hajj Fund Financial Management: A Bibliometric Analysis - Maysyaroh, Siti; Pratiwi Ch, Siti Angelina; Mawaddah; Saputri, Sukma Winnata; Humairah, Andi; Khomsatun, Siti (Halal Tourism and Pilgrimage, 2024)
This paper aims to explore the accountability and transparency of Hajj fund management through bibliometric analysis and data examination. This study uses paper publication data sourced from various research journals on the theme of Hajj fund management. The data was collected within the last 10 years. As a result, there were 103 publications related to the theme of "Accountability and Transparency Hajj Funds Management" in the period 2014-2023. In addition, the development trend of Hajj funds management publications was analyzed using VOS Viewer. This research method can be described as a descriptive approach based on bibliometric analysis. The data used in this study came from Hajj fund management publications taken from the Google Scholar database. The results of the study show that some popular topics and keywords are used in this theme and have the potential to be developed further. In addition, some of the most prolific journals and authors can be used as reference considerations for researchers to further explore this topic. This study only focuses on knowing the development trend of keywords, authors and journals published on the theme of Accountability and Transparency of Hajj Fund Financial Management, thematic evolution that describes the development of keywords, then the production of top authors over time which shows the productivity of authors.